Aging: The triumph of humanity-are we prepared to face the challenge? - Zile Singh (Wolters Kluwer Medknow Publications, 2012)
Advances in medicine have increased the life expectancy resulting in an increase in the geriatric population all over the world, and their proportion will only continue to rise in the coming years. It is known that the elderly bear a significant burden of morbidity, which is why health systems globally spearheaded by the WHO are waking up to the need for better geriatric health services. This includes India, whose health system continues to grapple with the health challenges of communicable and noncommunicable diseases. This article enumerates the various government policies and programs, constitutional and legal provisions available for the care of the elderly, and concludes that they are grossly inadequate to deal with the various physical, psychological, and emotional needs of the aging population. Mainstreaming of geriatric health to address the health needs of the elderly at all levels of health care, both in the public and the private sectors, giving due importance to multidimensional rehabilitative services and terminal care, involving NGOs and voluntary organizations, and stepping up social security in old age are the recommended measures for improving geriatric health in India.